Vulnerable users: deceptive robotics. Issue 3 (3rd July 2017) - Collins, Emily C.
ABSTRACT: The Principles of Robotics were outlined by the EPSRC in 2010. They are aimed at regulating robots in the real world. This paper represents a response to principle number four which reads: "Robots are manufactured artefacts. They should not be designed in a deceptive way to exploit vulnerable users; instead their machine nature should be transparent". The following critique questions the principle's validity by asking whether it is correct as a statement about the nature of robots, and the relationship between robots and people. To achieve this, the principle is broken down into the following two main component statements: (1) "Robots should not be designed in a deceptive way to exploit vulnerable users", and, (2) "Machine nature should be transparent". It is argued that both of the component statements that make up this principle are fundamentally flawed because of the undefined nature of the critical terms: "deceptive", "vulnerable", and "machine nature", and that as such the principle as a whole is misleading.